2011
DOI: 10.1097/wnr.0b013e32834a8990
|View full text |Cite
|
Sign up to set email alerts
|

The attentional blink demonstrates automatic deviance processing in vision

Abstract: Rare deviations in serial visual stimulation are accompanied by an occipital N2 in the event-related potential [the visual mismatch negativity (vMMN)]. Recent research suggests that the vMMN reflects automatic processing of information on the sensory level as a basis for change detection. To directly test the hypothesis that the vMMN is independent from attention, a rapid-serial-visual-presentation paradigm was applied: Either 300 ms or 700 ms after the presentation of a target (T1) a rare position change was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 20 publications
(35 reference statements)
6
30
0
Order By: Relevance
“…It should be noted that participants were unaware, which conjunctions were frequent and which conjunctions were infrequent. The automatic nature of the vMMN is supported by recent findings (Berti, 2011).…”
Section: Representing Feature Combinationssupporting
confidence: 70%
“…It should be noted that participants were unaware, which conjunctions were frequent and which conjunctions were infrequent. The automatic nature of the vMMN is supported by recent findings (Berti, 2011).…”
Section: Representing Feature Combinationssupporting
confidence: 70%
“…Thus, an important issue is how the specificity of the automatic nature of visual MMN generation can be characterized. To date, this specificity has often been described as "pre-attentive" or "attention-independent", and this notion has been supported by previous studies which demonstrated that visual MMN was not modulated as a function of task difficulty (Heslenfeld, 2003;Pazo-Alvarez et al, 2004a) or direction of attention (Berti, 2011;Winkler et al, 2005). In contrast, however, it has also been reported that visual MMN was modulated as a function of task difficulty (Kimura et al, 2008d; see also Yucel et al, 2007) or direction of attention (Czigler and Sulykos, 2010;Flynn et al, 2009;Kimura et al, 2010d).…”
Section: Underlying Processesmentioning
confidence: 73%
“…Using an attentional blink paradigm, Berti (2011) investigated the potential involvement of attention in mismatch generation more directly. In this elegant experiment, irrelevant deviant stimuli (stimuli in deviant location) followed the target events at various lags in rapid serial visual presentation (RSVP) sequences.…”
Section: Introduction—what Is Visual Mmn and What Is It Good For?mentioning
confidence: 99%
“…A robust result of attentional blink studies is that if the target is followed by another target stimulus within an interval of ~100–500 ms, the probability of detecting the second target decreases (e.g., Dux and Marois, 2009). Berti (2011) observed vMMN in the attentional blink interval, indicating that no attentional processing is needed for the emergence of this ERP component.…”
Section: Introduction—what Is Visual Mmn and What Is It Good For?mentioning
confidence: 99%